Pedagogical conception of ICT conflicts in schools in the province of Malaga (Spain): A commitment to mediation. - González Sodis, José Luis; Leiva-Olivencia, Juan José; Matas-Terrón, Antonio (Universidad Pablo de Olavide, 2022)
Unwanted behaviour using Information and Communication Technologies (ICT), generally with mobile phones, is a concern in schools in our country. In order to address this situation, new strategies are being developed and applied to promote positive coexistence, such as peer mediation. The aim of this research is to analyse how ICT conflicts are perceived by students in Compulsory Secondary Education (ESO). A survey study was carried out using a Likert-type questionnaire, the School Violence Questionnaire (CUVE-R) on the perception of conflicts. The sample consisted of 1069 students from different schools in Malaga. The results indicate the existence of a significant level of ICT conflict between pupils and, to a lesser extent, between pupils and teachers, always from the pupils' point of view. It is concluded that ICT violence can be tackled with the implementation of school mediation, a strategy that is proposed as an appropriate procedure for positive conflict management. The fundamental principles of mediation are the same: voluntariness and free will, equality of the parties, neutrality of the mediators and confidentiality. In this paper we do not include cyberbullying behaviour as these authors consider that this conflict is the most serious of all possible conflicts and does not admit school mediation between peers as it does not support the elementary principle of equality between the parties, although mediation can be a good proactive strategy against cyberbullying.
Keywords: Escuelas; Redes sociales en Internet; Innovaciones tecnológicas; Resolución de problemas; School coexistence; Social networks; Information and Communication Technologies (ICT); I.C.T. viólense; Conflict perception; School mediation